Orality in the literature of Africa's Horn : oral traditions, forms and pastoral mythologies literature, marks of orality in the literature - (:unkn) unknown (My University, 2012)
The Horn of Africa has a traditional oral literature which is rich and varied as the rest of the continent, starting from pastoral mythology to poetry, legend and storytelling. But with the social upheaval which occurred with the arrival of European settlers and the introduction of writing, the chain of transmission of the oral tradition is threatened. Many Europeans have sought to describe the habits and customs of these people. Whereas on the other hand, the writers from the Horn of Africa are often inspired by giving it (orality) and a new way of doing it. The following research work strives to reflect traditional forms of orality and their impact on modern literature.
Keywords: African Research